Cardioprotective Effects of Red Ginger Extracted Using Natural Deep Eutectic Solvent on Lipid Profile in Atherosclerotic Rats - Yulianita; Herlina, Nina; Tri Retno Handayani, Marybet; Al Aziz, Novan Masis; Safitri, Aditiya; Pamungkas, Ragil Raihan (Jurnal Jamu Indonesia, 2025)
Atherosclerosis, a leading cause of cardiovascular disease, is closely related to dyslipidemia. This study evaluated the cardioprotective effects of red ginger (Zingiber officinale var. rubrum) extracted using a Natural Deep Eutectic Solvent (NADES) on lipid profiles and the risk of atherosclerosis in rats induced with an atherogenic diet and lipopolysaccharide (LPS). Thirty male Sprague-Dawley rats were divided into five groups: normal control, negative control, positive control (Simvastatin), and two treatment groups receiving red ginger extract at 25 mg/kg and 50 mg/kg body weight (BW). After 24 days of treatment, the 25 mg/kg BW dose significantly reduced total and LDL cholesterol while increasing HDL levels compared with the negative control (p < 0.05), showing comparable effects to Simvastatin. The 50 mg/kg BW dose did not significantly reduce total and LDL cholesterol but produced the highest HDL level. All treatment groups showed a significantly lower Atherogenic Index of Plasma (AIP) than the negative control, with the lowest AIP in the 50 mg/kg BW group. These findings demonstrate the cardioprotective potential of red ginger extracted with NADES as a natural, environmentally friendly approach to preventing dyslipidemia and atherosclerosis.